2015
DOI: 10.1111/joor.12286
|View full text |Cite
|
Sign up to set email alerts
|

Association of GDF5, SMAD3 and RUNX2 polymorphisms with temporomandibular joint osteoarthritis in female Han Chinese

Abstract: Temporomandibular joint osteoarthritis (TMJOA) is a complex disease and has a strong genetic component in its pathogenesis. Experimental evidence suggests the involvement of biological pathway in the disease. This case-control study was designed to investigate whether five common single nucleotide polymorphisms (SNPs) in GDF5, SMAD3, RUNX2, TGFβ1 and CHST11, respectively, are associated with TMJOA in female Han Chinese patients. A total of 240 participants were evaluated comprising 114 female patients diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Moreover, OA cases were defined with different criteria in different studies, which might be one of sources of observed heterogeneity. Some studies defined their patients using the K/L classification and/or ACR criteria [29][30][31][32][33][34][35]37,[39][40][41][42][43], while other studies defined their patients using the TKR [28,36,38]. This discrepancy on those key characteristics of the participants,such as age and BMI, might also lead to the heterogeneity [34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, OA cases were defined with different criteria in different studies, which might be one of sources of observed heterogeneity. Some studies defined their patients using the K/L classification and/or ACR criteria [29][30][31][32][33][34][35]37,[39][40][41][42][43], while other studies defined their patients using the TKR [28,36,38]. This discrepancy on those key characteristics of the participants,such as age and BMI, might also lead to the heterogeneity [34].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining studies (n=38) were reviewed and additional 22 studies were excluded for not being case-control or cohort studies (n=6), not relevant to the GDF5 gene (n=3), not related to OA or LDD (n=7), or unavailable genotyping data (n=6). In the final analysis, there were 15 articles that were combined to perform an association analysis of rs143383 with OA and/ or LDD [28][29][30][31][32][33][35][36][37][38][39][40][41][42][43].The characteristics of these included articles were presented in Table 1. All the studies conformed to HWE in the control group.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…van de Laar et al revealed that mutations in SMAD3 could contribute to increased aortic expression of several key members in the TGF‐β pathway including SMAD3, which showed significant correlation with early‐onset OA. Recently, 5 studies (2 Caucasian studies and 3 Asian studies) explored the association between SMAD3 rs12901499 polymorphism and risk of OA, but with conflicting results . Some studies have shown that SMAD3 rs12901499 polymorphism was associated with OA risk .…”
Section: Introductionmentioning
confidence: 99%